Pengaruh Gaya Hidup Konsumtif Dan Hedonisme Terhadap Keputusan Konsumen Dalam Pembelian Barang Di Shopee Perspektif Ekonomi Islam - Anisa Binar Cahyani (Business and Enterpreneurship Journal (BEJ), 2023)
The purpose of this study was to determine the effect of a consumptive lifestyle and hedonism on consumer decisions in purchasing goods at shopee according to an Islamic economic perspective. The data used is primary data. Furthermore, the data collection technique used in this study was distributing questionnaires to respondents who used the Google form to collect data. In this study the researchers used the t test method and coefficient test with the help of the smart pls program version 3. Based on the results of the research the R² value lies at 0 R² 1, an R² value close to one which means the model is getting better. Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table where R² 1 with a value of 0 1,000 1, this means that the variance of the consumptive lifestyle and hedonism is able to explain the variance of consumer decisions by 100%. Keywords : Consumptive Lifestyle, Hedonism, and Consumer Decisions